The Effect of A Virtual Laboratory-Assisted Inquiry-Based Learning Model on Students' Science Process Skills: A Systematic Literature Review - Robiatul Adawiah; Aulia Aulia; Lutfiatussolihah Lutfiatussolihah; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2026)
Science Process Skills (SPS) are essential for developing students' conceptual understanding and scientific thinking. However, teacher-centered instruction and limited laboratory facilities hinder optimal SPS development. This study aims to analyze and synthesize the impact of Inquiry-Based Learning assisted by virtual laboratories on students' SPS using a Systematic Literature Review (SLR) approach. Literature was gathered from national and international journals (Google Scholar, ProQuest, ERIC) published between 2016 and 2025. Guided by PRISMA 2020 protocols across four selection stages, 15 relevant articles were systematically analyzed using qualitative descriptive methods. The findings reveal a consistent positive effect on SPS specifically observing, hypothesizing, experimenting, data analyzing, and communicating alongside increased student engagement. Effectiveness depends on inquiry type, teacher guidance, and instructional design. Although virtual labs cannot fully replace hands-on manipulative skills, this integrated approach offers an effective, flexible alternative for science education.